2009
DOI: 10.1021/cm8030895
|View full text |Cite
|
Sign up to set email alerts
|

Leakage and Proton Conductivity in the Predicted Ferroelectric CsBiNb2O7

Abstract: The layered perovskite CsBiNb 2 O 7 has been reinvestigated in the light of recent predictions of ferroelectric behavior. Variable temperature powder neutron diffraction experiments show that this material retains polar symmetry (space group P2 1 am) up to at least 900 °C, with only a slight decrease in net polarization up to this temperature, calculated using a simple ionic model. However, ac impedance measurements show only a modest dielectric constant (19-27) throughout the temperature range studied. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 28 publications
4
49
0
Order By: Relevance
“…The product of R 1 and R 2 establishes the polar space group symmetry, P ∼ R 1 ⊕ R 2 . This is a rather general mechanism that can induce ferroelectricity in many families of layered oxides; 7,10,[126][127][128][129][130][131][132] see Ref. 133 for a recent review.…”
Section: E Putting It All Together: Similarities Between Lioso3 Dopmentioning
confidence: 99%
“…The product of R 1 and R 2 establishes the polar space group symmetry, P ∼ R 1 ⊕ R 2 . This is a rather general mechanism that can induce ferroelectricity in many families of layered oxides; 7,10,[126][127][128][129][130][131][132] see Ref. 133 for a recent review.…”
Section: E Putting It All Together: Similarities Between Lioso3 Dopmentioning
confidence: 99%
“…As reported in early experimental and theoretical work on the Dion-Jacobson CsBiNb 2 O 7 compound, one of the most important ingredients is octahedral tilting [17][18][19][20]. The room temperature structure of CsBiNb 2 O 7 is a Pmc2 1 orthorhombic structure [21] with a − a − c + tilting of the Glazer notation [21][22][23][24].…”
mentioning
confidence: 95%
“…Their calculation clearly showed that the coupling of the zone-center ferroelectric mode and zone-boundary octahedral tilting mode is the key origin for ferroelectric realization of a CsBiNb 2 O 7 material. Experimentally, the ferroelectric nature of CsBiNb 2 O 7 is unclear because of the large ionic conductivity of this material [19].…”
mentioning
confidence: 99%
“…Later, Fennie and Rabe predicted ferroelectricity in CsBiNb 2 O 7 from a first-principles DFT study [15]. Our follow-up experimental studies [16] on CsBiNb 2 O 7 suggested that ferroelectricity was hindered by moisture uptake, leading to proton conductivity and leakage. Nevertheless, a more recent work by Chen et al [17] did provide experimental evidence for ferroelectricity in this compound.…”
Section: Introductionmentioning
confidence: 59%
“…Nevertheless, a more recent work by Chen et al [17] did provide experimental evidence for ferroelectricity in this compound. Goff et al [16], attempted to determine any high temperature phase transitions in CsBiNb 2 O 7 using powder neutron diffraction: no evidence for phase transitions was identified up to 900 • C, above which sample deterioration precluded further study. By analogy with CsNdNb 2 O 7 , we speculated that La-doping of CsBiNb 2 O 7 would reduce the orthorhombic distortion such that any phase transition to higher symmetry might be brought down in temperature relative to that of CsBiNb 2 O 7 , and make this transition more amenable to experimental study.…”
Section: Introductionmentioning
confidence: 99%